LAUTAN SEBAGAI RUMAH: MAKNA SEMIOTIK PUISI SUFI SEASHELL VOICE KARYA TIEL AISHA ANSARI - ., Taufiqurrohman (Proceeding SENDI_U, 2015)
This study of Tiel Aisha Ansariâs Sufi poem entitled Seashell Voice is aimed at knowing themeaning of âoceanâ / âseaâ expressed. It is also to know the uniqueness of using the term in aSufi poem. The writer of this essay uses Riffaterre semiotic theory to analyse the meaning of thepoem. This is due to the totality of this theory in interpreting a poem starts at analyzing surfacemeaning to core meaning. The result of analysis on the poem Seashell Voice shows that this poemuses the main signifier âseaâ / âoceanâ and âseashellâ. The âseaâ actually becomes the symbolfor home that is longed so much by the âseashellâ. Then the second meaning has been got is thatseashell symbolizes man / human himself. The man is always eager to be with his God that hasbeen symbolized as sea. The conclusion can be got from the study of Seashell Voice poem is thatsea symbolizes God Himself as been written in many Sufi poems. Man that is symbolized withseashell felt far from his God. Thatâs why he longs very much to go back to his original home,namely God.Keywords : sea, Sufi poem, symbol, God